What happens to brain outside the thermal ablation zones? An assessment of needle-based therapeutic ultrasound in survival swine. (31st December 2022) - Szewczyk, Benjamin; Tarasek, Matthew; Campwala, Zahabiya; Trowbridge, Rachel; Zhao, Zhanyue; Johansen, Phillip M.; Olmsted, Zachary; Bhushan, Chitresh; Fiveland, Eric; Ghoshal, Goutam; Heffter, Tamas; Tavakkolmoghaddam, Farid; et al.
Abstract: Background: In stereotactic radiosurgery, isodose lines must be considered to determine how surrounding tissue is affected. In thermal ablative therapy, such as laser interstitial thermal therapy (LITT), transcranial MR-guided focused ultrasound (tcMRgFUS), and needle-based therapeutic ultrasound (NBTU), how the surrounding area is affected has not been well studied. Objective: We aimed to quantify the transition zone surrounding the ablation core created by magnetic resonance-guided robotically-assisted (MRgRA) delivery of NBTU using multi-slice volumetric 2-D magnetic resonance thermal imaging (MRTI) and subsequent characterization of the resultant tissue damage using histopathologic analysis. Methods: Four swine underwent MRgRA NBTU using varying duration and wattage for treatment delivery. Serial MRI images were obtained, and the most representative were overlaid with isodose lines and compared to brain tissue acquired postmortem which underwent histopathologic analysis. These results were also compared to predicted volumes using a finite element analysis model. Contralateral brain tissue was used for control data. Results: Intraoperative MRTI thermal isodose contours were characterized and comprehensively mapped to post-operative MRI images and qualitatively compared with histological tissue sections postmortem. NBTU 360° ablations induced smaller lesion volumes (33.19 mm 3 ; 120 s, 3 W; 30.05 mm 3, 180 s, 4 W) versus 180° ablations (77.20 mm 3, 120 s, 3 W; 109.29 mm 3 ; 180 s; 4 W). MRTI/MRI overlay demonstrated the lesion within the proximal isodose lines. The ablation-zone was characterized by dense macrophage infiltration and glial/neuronal loss as demonstrated by glial fibrillary acidic protein (GFAP) and neurofilament (NF) absence and avid CD163 staining. The transition-zone between lesion and normal brain demonstrated decreased macrophage infiltration and measured ∼345 microns ( n  − 3). We did not detect overt hemorrhages or signs of edema in the adjacent spared tissue. Conclusion: We successfully performed MRgRA NBTU ablation in swine and demonstrated minimal histologic changes extended past the ablation-zone. The lesion was characterized by macrophage infiltration and glial/neuronal loss which decreased through the transition-zone.